The Effectiveness of Peppermint Aroma Therapy on Menopause Women’s Anxiety in Serang Village - Siska Supriwianti; Lili Anggraini (STIKep PPNI Jawa Barat, 2023)
Aims: as many as 39.4% of 71 women experience anxiety in the severe category. One of the contributing factors is the lack of knowledge about menopause. The large number of menopausal women represents the readiness of women to accept the changes that occur during that period. This unpreparedness is motivated by several factors, including: lack of understanding/knowledge, education, environment and so on. Objectives: To Know The Effectiveness Of Giving Peppermint Aromatherapy In Reducing Anxiety In Menopausal Mothers In Serang Village In 2022 Methods: The type of research in this research is quantitative. This research is a type of experimental research. This research will be carried out in Serang Village from October to November 2022 with the assistance of the local RT and RW heads. The reason for taking in the village of Serang is because the distance to the house is very close and you know the environment where menopausal women live. The number of samples in this study was 30 respondents. With the total sampling technique where 15 respondents were examined and given aromatherapy and 15 respondents were not examined and both used a questionnaire. The instruments used were the HARS Questionnaire and SOP for lemon aromatherapy. After that, the researchers processed the data using the t-test. Results: From the results of the analysis of the t-test data, the results obtained are p = 0.000. This figure indicates that the p value <0.05, meaning that there is an effect of giving peppermint aroma therapy on the anxiety of menopausal mothers. Conclusion: There is an Effect of Giving Peppermint Aromatherapy on Anxiety of Menopausal Mothers. It is hoped that this research can provide a means of information or knowledge about the effect of Peppermint Aromatherapy on Anxiety of Menopausal Mothers.